2022
DOI: 10.3389/fped.2022.919879
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma levels of PDGF-BB, VEGF-A, and HIF-2α in preterm infants after ibuprofen treatment

Abstract: IntroductionIbuprofen is one of the most common non-steroidal anti-inflammatory drugs used to close patent ductus arteriosus (PDA) in preterm infants. PDA is associated with bronchopulmonary dysplasia (BPD), while PDA closure by ibuprofen did not reduce the incidence of BPD or death. Previous studies have indicated an anti-angiogenesis effect of ibuprofen. This study investigated the change of angiogenic factors after ibuprofen treatment in preterm infants.MethodsPreterm infants with hemodynamically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The absolute risk difference between the two groups was −17.6 percentage points, with a 95% confidence interval ranging from −30.2 to −5.0 [ 85 ]. This higher risk of moderate-to-severe BPD in the intervention group may be related to a decrease in vascular growth factors in preterm infants after exposure to ibuprofen [ 86 ].…”
Section: Pathogenesis Of Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…The absolute risk difference between the two groups was −17.6 percentage points, with a 95% confidence interval ranging from −30.2 to −5.0 [ 85 ]. This higher risk of moderate-to-severe BPD in the intervention group may be related to a decrease in vascular growth factors in preterm infants after exposure to ibuprofen [ 86 ].…”
Section: Pathogenesis Of Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Similarly, the anti-angiogenic effect of ibuprofen might be absent if given at a later stage when vascular growth is less vulnerable. We have recently demonstrated that ibuprofen reduces vascular growth factors, such as PDGF-BB, VEGF-A and HIF-2ɑ, in infants with PDA [ 59 ], confirming that the anti-angiogenic effect of ibuprofen is already present in human infants exposed for 3 days. Although this adverse effect on vascular growth might be absent when ibuprofen is given at a later stage, it may compromise its positive effect on PDA closure.…”
Section: Discussionmentioning
confidence: 78%
“…26,27 A recent prospective study showed decreased vascular growth factors in preterm infants with PDA after exposure to ibuprofen. 28 Of note, previous randomized trials have not shown an increase in the risk of bronchopulmonary dysplasia with ibuprofen treatment. It is possible that this discrepancy can be explained by the high percentage of infants who received open-label treatment in the expectant-management group in these trials.…”
Section: Discussionmentioning
confidence: 98%